Optimizing the Energy Production for a Photovoltaic Thermal (PVT) Water System - Alsayegh, Khader M.J. (2022)
A Master of Science thesis in Mechanical Engineering by Khader M.J. Alsayegh entitled, “Optimizing the Energy Production for a Photovoltaic Thermal (PVT) Water System”, submitted in May 2022. Thesis advisor is Dr. Mohamed O. Hamdan and thesis co-advisor is Dr. Mehmet F. Orhan. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).